Modified porous carbon material and preparation method thereof

The modified porous carbon material prepared by multi-stage modification treatment solves the problem of high temperature of catalytic oxidation H2S reaction in the prior art, improves the specific surface area and catalytic performance of the material, and achieves a low-temperature and efficient H2S conversion effect.

CN119733481APending Publication Date: 2025-04-01TONGJI UNIV
1 Cites 0 Cited by

Patent Information

Application Number
CN202510009589.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

When existing porous carbon materials catalyzed hydrogen sulfide (H2S), the reaction temperature is high, which increases cost and energy consumption.

Method used

By using hyaluronic acid and chitosan as raw materials and undergoing multi-stage modification treatment, a modified porous carbon material with high specific surface area and excellent adsorption performance was prepared, and its catalytic performance was further improved by the treatment of potassium hydroxide and active metal salt.

Benefits of technology

The specific surface area and adsorption properties of modified porous carbon materials are significantly improved, especially under low temperature conditions, which improves the conversion rate of H2S and reduces the temperature and cost of the catalytic reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119733481A_ABST
    Figure CN119733481A_ABST
Patent Text Reader

Abstract

The invention provides a modified porous carbon material and a preparation method thereof, and belongs to the technical field of porous carbon materials. According to the preparation method, hyaluronic acid and chitosan are taken as raw materials, sodium chloride is taken as a pore-forming agent to prepare high-molecular hydrogel with a porous structure, then high-temperature carbonization is performed in ammonia gas to obtain a nitrogen-doped porous carbon material, and potassium hydroxide is used for modifying the nitrogen-doped porous carbon material, so that the specific surface area and physical and chemical properties of the material are improved; the loading stability between the carrier and the metal ions is improved; and finally, further modifying by loading metal ions to obtain the modified porous carbon material. The modified porous carbon material disclosed by the invention is subjected to multi-stage modification, so that the specific surface area and the adsorption performance of the carbon material are improved, and meanwhile, the H2S catalytic oxidation performance of the carbon material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of porous carbon materials, and in particular to a modified porous carbon material and a preparation method thereof. Background Art

[0002] Porous carbon is a porous material with carbon as its skeleton. It has a huge surface area and is widely considered to be a promising adsorbent. Porous carbon materials include activated carbon, activated carbon fibers, carbon nanotubes, ordered mesoporous carbon, new polymer-based carbon, doped porous carbon, graphene sheets, etc.

[0003] In recent decades, porous carbon materials have attracted widespread attention in the fields of chemistry, physics, and materials science.

[0004] Carbon-based nanocomposite adsorbents can be used not only for the adsorption of exhaust gas, but also for the adsorption of pollutants in wastewater. Its adsorption performance is mainly affected by two factors: one is the composition of the material itself, and the other is the spatial structure of the material. Among the components of the material, active substances mainly play an adsorption role. Different active substances and their contents have a great influence on the adsorption effect. Of course, the active substances need to be loaded on the skeleton material to exert the maximum adsorption effect. Although the skeleton material has no significant adsorption capacity for the adsorbate, as a component of the adsorbent material, on the one hand, it can fix the active substance and prevent the loss of the active substance during the adsorption process; on the other hand, it can adjust the spatial structure of the adsorbent material and change the specific surface area and pore structure of the adsorbent material.

[0005] Hydrogen sulfide (H2S) is a highly toxic and corrosive gas that can have adverse effects on industrial production, the ecological environment, and human health even at low concentration levels. Therefore, removing H2S from industrial gases is of great significance. Porous carbon materials have the advantages of high specific surface area and large pore volume, making them suitable for use as catalysts for the catalytic oxidation of H2S.

[0006] The catalytic oxidation of H2S by porous carbon materials is a very complex process, which usually includes three steps: physical adsorption, chemical adsorption and catalytic oxidation. Specifically, water vapor in the gas phase is adsorbed on the porous carbon material to form a water film on its surface; H2S and O2 in the gas phase diffuse and are adsorbed into the pores of the porous carbon material, and then dissolved in the water film; H2S dissociates into HS - At the same time, the adsorbed O2 is activated to O* and HS - It reacts with active oxygen species at the porous carbon material-water film interface to generate elemental sulfur. A small amount of elemental sulfur will be further oxidized to SO2, and sulfuric acid will be formed in the presence of O2 and water. The activation of O2 and the dissociation of H2S are considered to be the key steps in the catalytic oxidation of H2S.

[0007] Chinese patent CN110694659A discloses a method for preparing a layered porous nitrogen-doped carbon material, and uses the material to selectively catalyze and oxidize hydrogen sulfide. However, the temperature of the catalytic reaction is high, which increases the cost of the reaction. Summary of the invention

[0008] In order to solve the problems existing in the prior art, the present invention provides a method for preparing a modified porous carbon material. The present invention prepares the carbon material after multi-stage modification, and the preparation method improves the specific surface area and adsorption performance of the porous carbon material, and at the same time improves its catalytic oxidation performance of H2S.

[0009] In order to achieve the above object, the present invention provides the following technical solutions.

[0010] A method for preparing a modified porous carbon material comprises the following steps:

[0011] (1) mixing a hyaluronic acid aqueous solution and a chitosan aqueous solution, adding a cross-linking agent and mixing evenly to obtain a mixed solution; reacting the mixed solution at room temperature for 10 to 15 hours to cross-link and obtain a polymer hydrogel;

[0012] (2) drying the polymer hydrogel in step (1) to obtain a xerogel;

[0013] (3) carbonizing the dry gel in step (2) at high temperature in an ammonia atmosphere, then washing with deionized water for 3 to 4 times and drying to obtain a nitrogen-doped porous carbon material;

[0014] (4) immersing the nitrogen-doped porous carbon material in step (3) in a potassium hydroxide solution, stirring at 70 to 80° C. for 2 to 5 hours, taking out and drying to obtain an alkali-modified porous carbon material;

[0015] (5) Grind the alkali-modified porous carbon material of step (4) into powder, add deionized water to make a suspension, then add active metal salt, stir evenly, let stand for 10 to 30 hours, centrifuge, filter, and dry to obtain the modified porous carbon material.

[0016] Preferably, the hyaluronic acid aqueous solution in step (1) is an aqueous solution of hyaluronic acid and sodium chloride; the concentration of hyaluronic acid in the hyaluronic acid aqueous solution is 3-5 g / mL, and the concentration of sodium chloride is 5-10 g / mL; the concentration of chitosan in the chitosan aqueous solution is 7-8 g / mL.

[0017] Preferably, the volume ratio of the hyaluronic acid aqueous solution to the chitosan aqueous solution in step (1) is 1-3:1-3.

[0018] Preferably, the cross-linking agent in step (1) is glutaraldehyde, and the concentration of the cross-linking agent in the mixed solution is 0.1 to 0.2 g / mL.

[0019] Preferably, the drying temperature in step (2) is 50-60° C., and the drying time is 0.5-3 h.

[0020] Preferably, the high temperature carbonization in step (3) is to increase the temperature to 550-700° C. at a rate of 2-3° C. / min and heat for 2-5 hours.

[0021] Preferably, in step (4), the mass volume ratio of the nitrogen-doped porous carbon material to the potassium hydroxide solution is 1-7 g:10-15 mL; and the mass fraction of the potassium hydroxide solution is 10-15%.

[0022] Preferably, the concentration of the alkali-modified porous carbon material in the suspension in step (5) is 1 to 5 g / L.

[0023] Preferably, the active metal salt in step (5) is any one of zinc chloride, cobalt chloride and nickel chloride; and the concentration of the active metal salt in the suspension is 0.01 to 0.05 mol / L.

[0024] Another object of the present invention is to provide a modified porous carbon material prepared by the above method.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention provides a modified porous carbon material and a preparation method thereof. The present invention first uses hyaluronic acid and chitosan as raw materials and sodium chloride as a pore-forming agent to prepare a polymer hydrogel with a porous structure, then carbonizes it at high temperature in ammonia to obtain a nitrogen-doped porous carbon material, and modifies it with potassium hydroxide to improve the specific surface area and physical and chemical properties of the material, as well as the loading stability between the carrier and the metal ions; finally, it is further modified by loading metal ions to obtain a modified porous carbon material. The modified porous carbon material prepared by the present invention has improved specific surface area and adsorption performance through multi-stage modification, and at the same time improves its performance of catalytic oxidation of H2S. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The change of H2S conversion rate with temperature under the catalytic conditions of different modified porous carbon materials. DETAILED DESCRIPTION

[0028] The present invention will be further described below in conjunction with the embodiments.

[0029] In the specific embodiments of the present invention, raw materials not specifically described are all conventional raw materials in the art; methods not specifically described are all conventional methods in the art.

[0030] Example 1

[0031] A method for preparing a modified porous carbon material, comprising the following steps:

[0032] (1) adding hyaluronic acid and sodium chloride into deionized water to obtain a hyaluronic acid aqueous solution having a hyaluronic acid concentration of 5 g / mL and a sodium chloride concentration of 5 g / mL;

[0033] Adding chitosan to deionized water to obtain a chitosan aqueous solution with a chitosan concentration of 7 g / mL;

[0034] The hyaluronic acid aqueous solution and the chitosan aqueous solution are mixed at a volume ratio of 1:1, and a cross-linking agent, glutaraldehyde, is added to obtain a mixed solution, wherein the concentration of glutaraldehyde in the mixed solution is 0.2 g / mL; the mixed solution is reacted at room temperature for 10 hours for cross-linking to obtain a polymer hydrogel;

[0035] (2) drying the polymer hydrogel in step (1) to obtain a xerogel; the drying temperature is 50° C. and the drying time is 2.5 h;

[0036] (3) carbonizing the dry gel in step (2) at high temperature in an ammonia atmosphere, washing with deionized water three times, and drying to obtain a nitrogen-doped porous carbon material; the high temperature carbonization is to increase the temperature to 600° C. at a rate of 3° C. / min and heat for 3 h;

[0037] (4) mixing the nitrogen-doped porous carbon material of step (3) with a potassium hydroxide solution having a mass fraction of 15% in a mass volume ratio of 2 g:15 mL, stirring at 80° C. for 4 h, taking out and drying to obtain an alkali-modified porous carbon material;

[0038] (5) Grind the alkali-modified porous carbon material described in step (4) into powder, add deionized water to prepare a suspension of the porous carbon material with a concentration of 5 g / L, then add 0.02 mol / L of active metal salt (the molar ratio of zinc chloride to cobalt chloride is 1:1), stir evenly, let stand for 24 hours, centrifuge, filter, and dry to obtain the modified porous carbon material.

[0039] Example 2

[0040] A method for preparing a modified porous carbon material, comprising the following steps:

[0041] (1) adding hyaluronic acid and sodium chloride into deionized water to obtain a hyaluronic acid aqueous solution having a hyaluronic acid concentration of 5 g / mL and a sodium chloride concentration of 8 g / mL;

[0042] Adding chitosan to deionized water to obtain a chitosan aqueous solution with a chitosan concentration of 7 g / mL;

[0043] The hyaluronic acid aqueous solution and the chitosan aqueous solution are mixed at a volume ratio of 1:1.5, and a cross-linking agent glutaraldehyde is added to obtain a mixed solution, wherein the concentration of glutaraldehyde in the mixed solution is 0.2 g / mL, and the mixture is reacted at room temperature for 10 hours for cross-linking to obtain a polymer hydrogel;

[0044] (2) drying the polymer hydrogel in step (1) to obtain a xerogel; the drying temperature is 60° C. and the drying time is 2 h;

[0045] (3) carbonizing the dry gel in step (2) at high temperature in an ammonia atmosphere, washing with deionized water for 4 times, and drying to obtain a nitrogen-doped porous carbon material; the high temperature carbonization is to increase the temperature to 600° C. at a rate of 3° C. / min and heat for 3 h;

[0046] (4) mixing the nitrogen-doped porous carbon material of step (3) with a potassium hydroxide solution having a mass fraction of 15% in a mass volume ratio of 5 g:15 mL, stirring at 80° C. for 2 h, taking out and drying to obtain an alkali-modified porous carbon material;

[0047] (5) Grind the alkali-modified porous carbon material described in step (4) into powder, add deionized water to prepare a suspension of the porous carbon material with a concentration of 3 g / L, then add active metal salt cobalt chloride with a concentration of 0.02 mol / L, stir evenly, let stand for 20 hours, centrifuge, filter, and dry to obtain the modified porous carbon material.

[0048] Comparative Example 1

[0049] A method for preparing a modified porous carbon material, the steps are as described in Example 1, except that the specific method of step (3) of comparative example 1 is: carbonizing the dry gel described in step (2) at high temperature in a helium atmosphere, washing it with deionized water three times, and drying it to obtain a porous carbon material; the high-temperature carbonization is to increase the temperature to 600°C at a rate of 3°C / min and heat it for 3h.

[0050] The remaining steps are the same as in Example 1.

[0051] Comparative Example 2

[0052] A method for preparing a modified porous carbon material, the steps are the same as those in Example 1, except that the potassium hydroxide treatment in step (4) is not performed in Comparative Example 2.

[0053] The modified porous carbon materials prepared in Examples 1 to 2 and Comparative Examples 1 to 2 were subjected to the following tests:

[0054] 1. The specific surface area of ​​the material was tested by N2 adsorption-desorption, and the N content was tested by CHNS elemental analysis; the adsorption capacity of the material for CO2 in simulated flue gas (10% CO2, adsorption at room temperature and pressure) was tested by thermogravimetric analyzer. The test results are shown in Table 1.

[0055] Table 1

[0056] <![CDATA[Specific surface area m 2 / g]]> N content wt% <![CDATA[CO2 adsorption capacity mg / g]]> Example 1 1247 6.9 142 Example 2 1196 6.4 137 Comparative Example 1 268 0.3 65 Comparative Example 2 457 6.2 72

[0057] 2. The modified porous carbon materials prepared in Examples 1 to 2 and Comparative Examples 1 to 2 were used to carry out an experiment on catalytic oxidation of H2S. The specific method is as follows:

[0058] The modified porous carbon material is applied to the catalytic reaction of selective catalytic oxidation of H2S to sulfur and water, the reaction temperature is 20-200°C, the raw gas is a three-component gas of 5000ppm H2S, 2500ppm O2, and N2 as the balance gas, the catalyst dosage is 0.1g, and the raw gas flow rate is 20mL·min -1 , the inner diameter of the reaction tube is 5 mm.

[0059] The change of H2S conversion rate with temperature is as follows: Figure 1 .from Figure 1 It can be seen that the modified porous carbon material prepared in the examples of the present application significantly improves the conversion rate of H2S under low temperature conditions.

[0060] 3. The modified porous carbon materials prepared in Examples 1 to 2 and Comparative Examples 1 to 2 are used to adsorb pollutants in water. The specific method is as follows:

[0061] 35 mg of modified porous carbon material was added to 100 mL of enrofloxacin solution (enrofloxacin was 0.05 M), and the solution was shaken in a water bath at 25°C for 1 h. 1 mL of the solution was sampled to measure the concentration of enrofloxacin in the solution, and the removal rate was calculated. The results are shown in Table 2.

[0062] Table 2

[0063]

[0064]

[0065] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a modified porous carbon material, characterized in that: The following steps are involved: (1) mixing a hyaluronic acid aqueous solution and a chitosan aqueous solution, adding a cross-linking agent and mixing evenly to obtain a mixed solution; reacting the mixed solution at room temperature for 10 to 15 hours to cross-link and obtain a polymer hydrogel; (2) drying the polymer hydrogel in step (1) to obtain a xerogel; (3) carbonizing the dry gel in step (2) at high temperature in an ammonia atmosphere, then washing with deionized water for 3 to 4 times and drying to obtain a nitrogen-doped porous carbon material; (4) immersing the nitrogen-doped porous carbon material in step (3) in a potassium hydroxide solution, stirring at 70 to 80° C. for 2 to 5 hours, taking out and drying to obtain an alkali-modified porous carbon material; (5) Grind the alkali-modified porous carbon material of step (4) into powder, add deionized water to make a suspension, then add active metal salt, stir evenly, let stand for 10 to 30 hours, centrifuge, filter, and dry to obtain the modified porous carbon material.

2. The method for preparing a modified porous carbon material according to claim 1, characterized in that: The hyaluronic acid aqueous solution in step (1) is an aqueous solution of hyaluronic acid and sodium chloride; the concentration of hyaluronic acid in the hyaluronic acid aqueous solution is 3-5 g / mL, and the concentration of sodium chloride is 5-10 g / mL; the concentration of chitosan in the chitosan aqueous solution is 7-8 g / mL.

3. The method for preparing a modified porous carbon material according to claim 1, characterized in that: The volume ratio of the hyaluronic acid aqueous solution to the chitosan aqueous solution in step (1) is 1-3:1-3.

4. The method for preparing a modified porous carbon material according to claim 1, characterized in that: The cross-linking agent in step (1) is glutaraldehyde, and the concentration of the cross-linking agent in the mixed solution is 0.1-0.2 g / mL.

5. The method for preparing a modified porous carbon material according to claim 1, characterized in that: The drying temperature in step (2) is 50-60° C. and the drying time is 0.5-3 h.

6. The method for preparing a modified porous carbon material according to claim 1, characterized in that: The high temperature carbonization in step (3) is to increase the temperature to 550-700° C. at a rate of 2-3° C. / min and heat for 2-5 hours.

7. The method for preparing a modified porous carbon material according to claim 1, characterized in that: In step (4), the mass volume ratio of the nitrogen-doped porous carbon material to the potassium hydroxide solution is 1-7 g:10-15 mL; the mass fraction of the potassium hydroxide solution is 10-15%.

8. The method for preparing a modified porous carbon material according to claim 1, characterized in that: The concentration of the alkali-modified porous carbon material in the suspension of step (5) is 1 to 5 g / L.

9. The method for preparing a modified porous carbon material according to claim 1, characterized in that: The active metal salt in step (5) is any one of zinc chloride, cobalt chloride and nickel chloride; and the concentration of the active metal salt in the suspension is 0.01 to 0.05 mol / L.

10. A modified porous carbon material, characterized in that: Prepared according to the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Layered porous nitrogen-doped carbon material as well as preparation method and application thereof

    CN110694659A